Labor Supply of Retiring Couples and Heterogeneity in Household Decision-Making Structure - Zhiyang Jia (Statistics Norway, Research Department, 2005)
This paper analyzes the labor market participation behavior of retiring couples in Norway. To account for the unobserved heterogeneity in decision-making structure within the household, I formulate a mixed model by assuming there are two types of households, the cooperative type and the non-cooperative type. I assume that non-cooperative households behave according to a Stackelberg game with the male as the leader, while cooperative households engage in a cooperative bargaining process. The estimation results show that more than half of the households are of the non-cooperative type.
Keywords: D10; J26; 330; household labor supply; retirement; unobserved heterogeneity; mixed model